POWER FLOW IN A LOAD-CURRENT SENSORLESS SHUNT ACTIVE POWER FILTER - H. Tumbelaka, Hanny (Institute of Research and Community Outreach, 2007)
In this paper, power flow analysis of a three-phase four-wire system with a shunt active power filter in steady state is presented. The analysis begins with a mathematical model of the power inverter and continues to find the relationship of the real and imaginary power as well as zero sequence power in the grid, loads, and the inverter (AC and DC sides) for successful compensation. The system includes mixed non-linear loads with significant unbalanced components. The filter consists of a three-phase current-controlled voltage source inverter (CC-VSI) with a filter inductance at the AC output and a DC-bus capacitor. The CC-VSI is operated to directly control the AC grid current to be sinusoidal and in phase with the grid voltage. Computer simulation results verify the concept of the filter and the power flow. Abstract in Bahasa Indonesia : Dalam makala ini disajikan analisa aliran daya dari sistem tiga-fasa empat-kawat dengan sebuah shunt active power filter dalam keadaan ajek. Analisa dimulai dengan model matematika dari power inverter dan dilanjutkan dengan mencari hubungan antara daya nyata, imajiner, dan urutan nol pada sumber, beban, dan inverter (sisi AC dan DC) untuk proses kompensasi yang berhasil. Dalam sistem ini terdapat bermacam beban tidak linier yang juga tidak seimbang. Sedangkan filternya terdiri dari current-controlled voltage source inverter (CC-VSI) tiga fasa yang dilengkapi dengan induktansi filter pada keluaran AC dan kapasitor DC-bus. CC-VSI beroperasi untuk mengendalikan arus sumber AC secara langsung agar menjadi sinus dan sefasa dengan tegangan sumber. Hasil simulasi komputer bersesuaian dengan konsep dari filter dan aliran daya. Kata kunci:active power filter, aliran daya